Desenvolvimento de aplicativo de teleinterconsulta em disfunção temporomandibular - Muniz, Isis de Araújo Ferreira (2023)
Introduction: Teleinterconsultation is a subdivision of teledentistry in which it allows the management of the patient by one or more professionals who can discuss the case report and conduct it remotely, synchronously, in real-time, or asynchronously. In this way, it represents the solution for the continuity of dental practice using information technology, mainly for temporomandibular disorders (TMD), which is the most frequent cause of chronic pain of non-dental origin in the orofacial region. Aim: To develop a teleinterconsultation application for diagnosing TMD and to evaluate its usability, viability, usefulness and diagnostic agreement. Materials and methods: The application was developed using the App Glide (GoogleTM) as a basis and was evaluated by five TMD expert judges, who tested the application for a week regarding feasibility, usability, and usefulness. The answers were according to the Likert scale, with values from 1 (totally disagree) to 5 (totally agree). The instrument used for the evaluation corresponded to a questionnaire adapted from Google Forms. For the analysis of the diagnostic agreement, case reports inserted in the application after the face-to-face evaluation and subsequently analyzed by the consultants were used. Results: It is a hybrid application, compatible with Android and iOS systems and which consists of a main screen with the concept of DTM, the purpose of the application, information about privacy and legality, instructions on its use, and guidelines on filling out the DC/TMD forms, and all this information contains images or instructional videos. The application also features a menu bar with interchangeable screens containing the professionals' registration, case reports, consultant's opinion, DC/TMD forms, and face-to-face assistance with the servicesavailable for assistance. The application is available and can be installed through the link: https://dtmapp.glideapp.io. The evaluation of the tool by the expert judges was satisfactory, being considered viable, easy to use, and useful for professionals. It was possible to observe diagnostic correspondence in 9 diagnoses by analyzing 11 case reports, evaluated in person and through the application. Conclusion: Given the results of this research, it is possible to conclude that the developed application can be used to assist the dental surgeon in the diagnosis, guidance and first care of patients with TMD.